How Do We Get People to Interact? International Students and the American Experience - Geary, Danielle (Journal of International Students, 2016)
American colleges and universities consider diversity a way to foster personal growth and a healthy society, challenge stereotypes, encourage critical thinking, and help students communicate and feel comfortable with people they may perceive to be different. Quality interaction that has the potential to grow into authentic relationships between Americans and international students may be the bridge to affecting these outcomes, but how do we get people to interact? In this article, based on research as well as her own experience as an international student, the author explores some of the challenges international students face and suggests ideas for sparking interaction between international students and Americans.